Changes in classroom environment and teacher-student relationships during the transition from primary to secondary school. - Ferguson, Peter D. (Curtin University, 1998)
This study investigated students' perceptions of the generalist learning environment of the primary school compared to the same students' perceptions of the learning environments of the secondary school, with a particular focus on science learning environments. The role of student sex and school size pathways were investigated as factors Influencing changes in students' learning environment perceptions. The same students' perceptions of the learning environment were collected in the final stages of primary school and again after their initial term in secondary school. Data collected were both qualitative and quantitative in nature, with the quantitative data derived from short forms of the My Class Inventory and the Questionnaire on Teacher Interaction. Insights were gained into how students' perceptions of learning environment, including the teachers' interpersonal style, changed during their first exposure to secondary learning environments and teachers, and how these changes in perceptions during transition depended upon school size and student sex. The study found that students' perceptions of the learning environments did change across transition, but that these changes on some scales varied with student sex and school size pathway.